Teachers' Experiences in Integrating Local Wisdom with Merdeka Curriculum through Differentiated Learning - Ulfarianti, Finia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article presents the results of a survey and focus group discussions (FGDs) aimed at exploring teachers' experiences in integrating local wisdom into the Merdeka Curriculum through differentiated learning. This article involves teachers from various disciplines who have just started implementing the Merdeka Curriculum in their schools. As a result, although teachers have a strong intention to implement differentiated learning, they still face many challenges. One of them is an in-depth understanding of the concept, limited training, and lack of supporting facilities. Local wisdom actually has great potential to enrich students' learning experience, but its integration is still minimal. Teachers feel the need to map students' readiness and interest in learning, and get more in-depth training so that they can optimally utilize local wisdom.